Uzun vadeli konut finansmanı sisteminin (mortgage) Türk konut sektörü içerisindeki yeri ve satınalma eğiliminin belirlenmesine yönelik uygulama II - (:unkn) unknown (My University, 2010)
İki bölümden olusan çalısmanın bu bölümünde, mortgage sisteminin Türk konut sektöründeki yeri niteliksel ve niceliksel incelenmis ve satınalma cephesindeki eğilimin belirlenmesi amacıyla bir anket çalısması yapılarak bulgular yorumlanmıstır.

In the second part of this paper, implications of mortgage system and marketing strategies of Turkish domicile sector have been determined in terms of qualitative and quantitative aspects. And also a survey has been done and findings were analysed to determine the demand aptitude of demand side.
The place of mortgage system in Turkısh domicile sector and an application for determining the inclination aptitude
Keywords: İktisat; Tarih; İşletme